Edge magnetism of triangular graphene nanoflakes embedded in hexagonal boron nitride. (25th January 2023) - Ge, Yang; Chen, Lingxiu; Jiang, Chengxin; Ji, Jianlong; Tan, Qiuyun; Pan, Douxing; Zhang, Wendong; Zhang, Riguang; Janzen, Eli; Edgar, James H.; Sang, Shengbo; Wang, Haomin
Abstract: Graphene nanoflakes (GNFs), with intriguing zigzag edge magnetism, have great potential for the application in high-speed and low-power nanoelectronics and spintronics. However, scattering from edge defects can substantially degrade this novel edge magnetism. Precisely controlled growth of GNFs with zigzag edges on dielectric substrates to suppress edge defect scattering is still challenging. Herein, we report the successful synthesis of triangular zigzag-edged GNFs via epitaxy on hexagonal boron nitride ( h -BN) templates. Further magnetic measurement results indicate the triangular zigzag-edged GNFs embedded in h -BN can induce the magnetization with a magnitude of 1e-4 emu/g at room temperature. Additionally, density functional theory calculations address such magnetic orderings originating from the superexchange interactions among local "unpaired" electrons located in the zigzag C−BN interface. Our in-plane hetero-integration approach to the template-epitaxial growth of GNFs on the pre-etched h -BN provides a promising platform for experimentally achieving GNFs with high electron spin states, which are highly desired for next-generation spintronics and nanoelectronics. Graphical abstract: Image 1